Стратегічне управління розвитком підприємств в енергетичній галузі - Чобіток, В.І.; Костін, Ю.Д. (Вісник економічної науки України, 2024)
У статті розглянуто сутність стратегії та стратегічного управління в діяльності енергетичних компаній. Автори визначають, що стратегічне управління розвитком компанії має відповідати її стратегії, при розробці якої враховуються внутрішнє та зовнішнє середовище, життєвий цикл продукції та компанії загалом, її фінансовий стан тощо. Приведена система стратегічного розвитку енергетичних компаній в контексті стратегічного управління. Акцент здійснюється на місію, як найголовнішу мету функціонування компанії, стратегічний аналіз, у результаті якого формуються стратегічні цілі розвитку енергетичної компанії, та систему прийняття управлінських рішень. Пропонуються заходи для реалізації покращення інфраструктурного забезпечення в системі стратегічного управління розвитком енергетичних компаній. The article defines the essence of strategic management and disclosed features of its development in the energy sector. The author notices the need to consider strategic development issues, because processes of globalization of economic activity, macropolitical situation and state of world economy, negative changes in the environment, strategic management issues as the basis of efficient development of energy companies are increasing. The author investigates the essence of strategic management issues, taking into account the experience of leading world scientists. The strategic management of the development of the energy company has to meet its strategy when developing which includes internal and external environments, the life cycle of products and companies in general, its financial state, etc. The characteristic of the mission is given as the most important goal of the company’s functioning, which determines the strategic direction of its development and a number of strategic goals. The mission must be simple, real, and relevant in the long term. The author gives the structure of the fuel and energy complex of Ukraine and proves the need to consider the development of energy companies. Specifically, the presence of atomic, hydropower, thermal, solar, wind energy, and the functioning of the energy sector generally creates significant obstacles to develop a single methodological approach to develop a single strategic management mechanism for the development of companies in the energy market. Strategic development of energy companies in the context of strategic management. According to the author’s strategic management of the development of the energy company is a tool for the management of the organization for flexible response and conducting timely changes in the organization, determining and achievement of goals that meet contemporary challenges, allowing for competing advantages that in the community to provide a steady competitiveness of the energy company.